1975
DOI: 10.1038/bjc.1975.90
|View full text |Cite
|
Sign up to set email alerts
|

Studies on mouse Moloney virus induced tumours: I. The detection of p30 as a cytotoxic target on murine Moloney leukaemic spleen cells, and on an in vitro Moloney sarcoma line by antibody mediated cytotoxicity

Abstract: Antigenic determinants of p30, the most abundant internal virion protein of C type RNA viruses, were detected on the surface of spleen cells from mice bearing Moloney leukaemia and on an in vitro line of Moloney sarcoma, MSC. On both cell types, these determinants on the p30 molecules served as cytotoxic targets in a xenogenic complement dependent antibody mediated 51Cr release assay. Two antisera were used: a rat anti MLV -M induced lymphoma serum, and an antiserum raised in goats to either disrupted FeLV. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

1975
1975
1982
1982

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…We have not studied this antiserum with MSC targets. Since our previous study (Epstein and Knight, 1975) (Epstein and Knight, 1975) indicated that this antiserum could detect antigenic determinants of p30, the most abundant internal virion protein of the C type RNA viruses on the surface of both of these targets. We found that as little as 0418 ,/g of a purified preparation of p30 obtained by isoelectric focusing could block 4300 of the cytotoxicity of this antiserum for MSC targets and 10000 of its cytotoxicity for M targets.…”
Section: Methodsmentioning
confidence: 97%
See 4 more Smart Citations
“…We have not studied this antiserum with MSC targets. Since our previous study (Epstein and Knight, 1975) (Epstein and Knight, 1975) indicated that this antiserum could detect antigenic determinants of p30, the most abundant internal virion protein of the C type RNA viruses on the surface of both of these targets. We found that as little as 0418 ,/g of a purified preparation of p30 obtained by isoelectric focusing could block 4300 of the cytotoxicity of this antiserum for MSC targets and 10000 of its cytotoxicity for M targets.…”
Section: Methodsmentioning
confidence: 97%
“…Details concerning the source and maintenance of Balb/c mice, passage of Moloney leukaemia in vivo and MSC cells in vitro, preparation of antisera and rabbit complement and performance of the 5'Cr release antibody mediated cytotoxicity test are described in the previous paper (Epstein and Knight, 1975 Absorption of antisera with mouse sera.-Various volumes of mouse serum (5-50 ,ul) were combined with either neat Rat ILR-3 or goat anti-gs3 and sufficient medium (Dulbecco's modification of Eagle's medium with glutamine (E-4-G1) supplemented with 10% normal rat or goat serum) to bring the antiserum to the dilution required in a final volume of 0-1 ml. The xenogeneic serum mixtures were kept at room temperature for 30 min and then employed in the 5ICr release assay.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations